The Contribution of the Al-Hasyimi Calligraphy Art Studio in Improving the Learning Outcomes of Arabic Language Education Students at UIN Datokarama Palu in the Al-Khat Course - Nursyam; Mohamad Idhan; Zaitun (Program Studi Pendidikan Bahasa Arab (PBA), Universitas Islam Negeri Datokarama Palu, 2025)
This study discusses the contribution of the Al-Hasyimi Calligraphy Art Studio in Palu in improving student learning outcomes in the Al-Khat course within the Arabic Language Education Program (PBA) at UIN Datokarama Palu. The main focus of this research is how the studio supports students’ mastery of calligraphy skills, particularly in the aspects of Arabic script aesthetics, writing techniques, and training discipline. Calligraphy is an essential skill in Arabic language learning; therefore, the presence of non-formal institutions such as calligraphy studios plays a strategic role in strengthening practical learning. This study employs a qualitative descriptive approach, with data collection techniques including observation, interviews, and documentation. The research subjects include the studio manager, lecturers of the Al-Khat course, and PBA students who are both active and inactive in participating in the studio’s training activities. The results show that students who actively participate in the studio's activities experience significant improvements in writing quality, understanding of various khat styles, and training discipline. The studio applies diverse teaching methods such as lectures, demonstrations, drills, evaluations, and the use of technology through infocus media, which effectively complement formal academic instruction on campus. Thus, the Al-Hasyimi Studio plays an important role as an educational partner in calligraphy learning, encompassing technical, aesthetic, spiritual, and professional dimensions. The studio not only complements formal classroom learning but also serves as a space for character formation and holistic student development. Therefore, collaboration between educational institutions and calligraphy studios is highly recommended to ensure effective and contextual learning.